2016
DOI: 10.3390/a9030052
|View full text |Cite
|
Sign up to set email alerts
|

Control for Ship Course-Keeping Using Optimized Support Vector Machines

Abstract: Support vector machines (SVM) are proposed in order to obtain a robust controller for ship course-keeping. A cascaded system is constructed by combining the dynamics of the rudder actuator with the dynamics of ship motion. Modeling errors and disturbances are taken into account in the plant. A controller with a simple structure is produced by applying an SVM and L2-gain design. The SVM is used to identify the complicated nonlinear functions and the modeling errors in the plant. The Lagrangian factors in the SV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Notably, in the study no asymptotic stabilization could be obtained in the case of external disturbance, which can be theoretically confirmed by Equations ( 26) and (37). Nevertheless, as remarked on the L2-gain inequality (22), the errors in the stabilization system were bounded and could be as small as possible by decreasing γ 1 in Equations ( 28) and (38), and increasing λ 1 in Equation (30) and λ 2 in Equation (39). Further verification was conducted using a course-unstable surface ship [28], the training ship model Blue Lady, as shown in Figure 9.…”
Section: Example Studymentioning
confidence: 87%
See 2 more Smart Citations
“…Notably, in the study no asymptotic stabilization could be obtained in the case of external disturbance, which can be theoretically confirmed by Equations ( 26) and (37). Nevertheless, as remarked on the L2-gain inequality (22), the errors in the stabilization system were bounded and could be as small as possible by decreasing γ 1 in Equations ( 28) and (38), and increasing λ 1 in Equation (30) and λ 2 in Equation (39). Further verification was conducted using a course-unstable surface ship [28], the training ship model Blue Lady, as shown in Figure 9.…”
Section: Example Studymentioning
confidence: 87%
“…As can be seen, the equality ( 21) contains the controller u 2 and the disturbance term, τ rw while the inequality (22) describes the performance of suppressing the disturbance τ rw . One can combine ( 21) with ( 22) in designing the controller u 2 to guarantee that the inequality (22)…”
Section: Controller Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Recall the above mentioned noticeable point about the requirement of dynamic models for ships, the former three models are not desirable fit. Trough the studies on the Nomoto model, it is reported to be applicable for control design especially the autopilot design in maritime engineering due to its simple structure and easy comprehension (Luo and Cong 2016) but its ability of capturing 1 DOF motions in yaw direction is not so expected to describe ship dynamics in particular used in ship´s motion simulation such as the MTS. Therefore, the task of how to match the requirement for the establishment of one dynamic model for different types of ships is deserved considerable study.…”
Section: Motivationmentioning
confidence: 99%
“…The polynomial kernel function is a global kernel function with strong generalization ability but weak learning ability [36], whereas the Gaussian radial basis kernel function is a local kernel function with strong learning ability but weak generalization ability. It is difficult to obtain good results in regression forecasting [37] by using only a single kernel function. Moreover, there are certain limitations in using the SVM with a single kernel function to predict the non-linear change in the data of the number of allocated containers of the container ship for one voyage.…”
Section: Construction Of Mixed Kernel Functionmentioning
confidence: 99%